Feminist economics editorial policies. (Feminist Economics, 2005)
The article focuses on the editorial policies of the periodical "Feminist Economics." Discussions of statistical results should report standard errors rather than t-statistics. Comments on statistical results should address the economic importance of the results. Statistical significance should be addressed only in the context of sample size and the economic meaningfulness of a coefficient.